A REVIEW OF ALZHEIMER’S DISEASE FORMATION, DIAG-NOSIS AND TREATMENT - Wang, Xueer (MATTER: International Journal of Science and Technology, 2020)
Alzheimer’s disease is one prevalent form of dementia associated with ageing, which is affecting approximately 1.3% of the UK population. Although the exact cause of Alzheimer’s disease remains unknown, it is widely accepted that the abnormal aggregation of proteins in the nervous system could be the primary cause resulting in this disease by damaging brain cells, and other risk factors also exist to increase the chances of having this disease such as ageing and a low education level. There are three possible distinct clinical phases in individuals with Alzheimer’s disease pathology: asymptomatic, mild cognitive impairment and Alzheimer’s disease. The symptoms of Alzheimer’s disease progression worsen gradually over several years which generally involve memory loss, motor coordination problems and inability to perform routine daily tasks. Because Alzheimer’s disease has a negative impact on not only the diagnosed patients but also their family members and the whole society, it is clear that treatment of this disease is required urgently. However, there is no current cure for Alzheimer’s disease but the symptoms can be managed and even moderated by a cohort of drugs as well as some protective factors. For example, aiming at various pathological symptoms of Alzheimer’s disease, different drugs have been investigated to resolve specific problems, thus help to control and alleviate the symptoms such as memory loss. There are also studies that discover numerous protective factors, which can reduce the risk of developing Alzheimer’s disease like a high education level and regular physical activities. Despite all the research and findings, the progress on Alzheimer’s disease is slow, and the prevention method is yet to be found, which means more attention and effort is needed to find an effective cure for this disease.